PENGARUH CORPORATE GOVERNANCE, PROFITABILITAS, UKURAN PERUSAHAAN, DAN KARAKTERISTIK EKSEKUTIF TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia) - Muttaqin, Ibnu; Alnur Dewi, Windi Niyyati; Nafi, Ilman (PERMANA, 2016)
This study aims to examine the effect of good corporate governace the extent of tax avoidance to companies manufacturing sector sub the food and beverage which is listed on the indonesia stock exchange . Elements of corporate governance that is used is the ownership of institutional, audits quality, independent commissioner, audit committee, profitability (return on assets), company size, and characteristic of executive (company risk). The population in this study was all companies manufacturing sector sub the food and beverage which is listed on the indonesia stock exchange 2011 until 2016. The study sample was determined by the purposive sampling method.The method of analysis that used is regression analysis multiple.The analysis showed that audits quality, audit committee, and company sizehas effect the tax avoidance. Whereas ownership institutional,independent commissioner, return on assets, and company risk has not effect the tax avoidance.Keywords: Corporate Governance, Ownership Institutional, Audit Quality, Independent Commissioner, Audit Committee, Return On Assets, Company Size, Company Risk , Tax Avoidance.